Lipids as competitive inhibitors of subtilisin carlsberg in the enzymatic hydrolysis of proteins in red tilapia (oreochromis sp.) viscera: insights from kinetic models and a molecular docking study (2019)
ABSTRACT: Protein hydrolysis can improve food’s nutritional, techno-functional and biological properties, which can increase the possibilities of application in industry. The objective of this research article was to study the effect of lipids on the enzymatic kinetics of red tilapia viscera (RTV) hydrolysis with subtilisin Carlsberg. The RTV were hydrolyzed in an enzyme/substrate ratio of 0.153 (U/g), at 53° C, at a pH of 9.5, initial concentrations of lipids of 1, 19 and 50 g/L, and different initial substrate concentrations for each initial lipid concentration. To explain the lipid action mechanism, we evaluated a Michaelis-Menten model and another semi-physical model based on kinetic expressions and mass balances. Additionally, a molecular docking analysis was performed between subtilisin Carlsberg and the main fatty acid in RTV (palmitic acid). For both models, the results suggest a strong competitive inhibition by lipids, with an inhibition constant of 2.36 and 3.01 g/L for the first and second models, respectively. On the other hand, docking suggested that palmitic acid could form van der Waals interactions and hydrogen bonds with the residues of the active site of subtilisin Carlsberg and occupy part of the substrate binding site, thus acting as an effective competitive inhibitor.